1889 Ariz. Sess. Laws 16-17, No. 13, § 3 - (:unkn) unknown (General Publisher, 1889)
Prohibiting carrying “a pistol or other firearm, dirk, dagger, slung shot, sword cane, spear, brass knuckles, bowie knife, or any other kind of a knife manufactured and sold for the purposes of offense or defense” to “any church or religious assembly, any school room, or other place where persons are assembled for amusement or for educational or scientific purposes, or into any circus, show or public exhibition of any kind, or to a ball room, social party or social gathering, or to any election precinct on the day or days of any election, where any portion of the people of this Territory are collected to vote at any election, or to any other place where people may be assembled to minister or to perform any other public duty, or to any other public assembly."
--
Keywords: CARRY - CERTAIN PUBLIC PLACES